1958
DOI: 10.1111/j.2044-8295.1958.tb00632.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Emotionality in the Rat

Abstract: A total of 112 rats (56 males and 56 females) is used to investigate the effects of some antecedent factors upon the defecation and ambulation scores derived from Hall's open‐field test of emotionality, given under precisely standardized conditions. Conditions of rearing and husbandry are similarly constant, except where systematically varied for experimental purposes. The results show that neither defecation nor ambulation is affected by systematic ‘gentling’. Sexual experience does not affect defecation, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
1
4

Year Published

1983
1983
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(75 citation statements)
references
References 0 publications
7
63
1
4
Order By: Relevance
“…White noise was chosen because it has also been found to modify stress-related behaviors (e.g. urination, defecation, trembling) in rats (Patrick 1931;Bindra and Thompson 1953;Broadhurst 1957) and it was of interest to determine if this type of stressor would affect circulating nicotine or rates of nicotine biotransformation.…”
Section: Environmental Stressmentioning
confidence: 99%
“…White noise was chosen because it has also been found to modify stress-related behaviors (e.g. urination, defecation, trembling) in rats (Patrick 1931;Bindra and Thompson 1953;Broadhurst 1957) and it was of interest to determine if this type of stressor would affect circulating nicotine or rates of nicotine biotransformation.…”
Section: Environmental Stressmentioning
confidence: 99%
“…In this test, an animal is simply placed into a novel, brightly lit arena from which escape is barred: the ambulation and the number of defecation in the field are often measured (Hall, 1934). The open-field test has been mainly validated in the rat, and it has been expected that the ambulation and the defecation have negative correlation (Broadhurst, 1957;Hall, 1934Hall, , 1936. Nevertheless, the test has also been widely used in mouse studies.…”
Section: Introductionmentioning
confidence: 98%
“…Broadhurst (1957) suggested that defecation is an index of emotionality and positively correlates well with it. Our data once more show that the BDR rats were emotionally hyporesponsive as demonstrated previously (Swain and Maric, 1995).…”
Section: Discussionmentioning
confidence: 97%